Controllable synthesis of SnS2 nanostructures with high adsorption and photocatalytic activities. (15th June 2017) - Zhang, Guimin; Du, Xiaodi; Wang, Yucheng; Wang, Hao; Wang, Weimin; Fu, Zhengyi
Abstract: Series of SnS2 nanostructures were synthesized by a facile refluxing process. Influencing factors on the microstructures and properties of SnS2 were investigated, including the reaction temperature, adding sequence of reagent and the solvent. The results indicated the as-prepared SnS2 products in lower temperature had larger surface areas and superior adsorption capability than that in higher temperature. SnS2 nanoflowers prepared at 120 °C in ethylene glycol exhibited remarkable adsorption capability for cationic dyes and heavy metal of Pb 2+, Cd 2+ . Intriguingly, the products also showed prominent visible light photocatalystic activity for Methyl Orange (MO). The formation mechanisms of different SnS2 nanostructures were proposed; the release of S 2- played a crucial role on controlling the morphology of SnS2 . The simple shape-controlled method can be extended to the synthesis of other metal sulfides and the high adsorption property is favorable to it coupling with other semiconductors or noble metals to far improve photocatalytic activity.